MoII Cluster Complex‐Based Coordination Polymer as an Efficient Heterogeneous Catalyst in the Suzuki–Miyaura Coupling Reaction. Issue 28 (30th August 2016) - Bůžek, Daniel; Hynek, Jan; Kučeráková, Monika; Kirakci, Kaplan; Demel, Jan; Lang, Kamil
Abstract : The design and preparation of highly active heterogeneous palladium catalysts is attracting ever‐increasing attention. In this paper, we report on the self‐assembly of palladium centers and an octahedral molybdenum cluster complex bearing phosphine terminal ligands. This leads to a coordination polymer exhibiting high catalytic activity in the Suzuki–Miyaura cross‐coupling reaction. The coordination polymer achieved a turnover number of 15800 in a reaction of deactivated aryl bromides with phenylboronic acid. Because metal clusters represent rare building blocks for the preparation of heterogeneous palladium catalysts, this work points to new structural motives that can be utilized to develop highly active heterogeneous catalysts. Abstract : A novel hexanuclear molybdenum cluster, bearing six phosphine terminal ligands, has been synthesized and its single‐crystal structure was determined. The combination of the cluster with Pd II centers formed a coordination polymer that displayed high catalytic activity in the Suzuki–Miyaura coupling reaction.